Case Report: Successful Treatment of Sarcoptic Mange in European Camelids - Georgiana Deak; Barbara Moroni; Ana Maria Boncea; Luisa Rambozzi; Luca Rossi; Andrei Daniel Mihalca (Frontiers in Veterinary Science, 2021)
Introduction: Members of the Camelidae family are very adaptable mammals, originating from South America. More recently, they have become popular in Europe as pets or wool production farm animals. Their dermatological problems refer mainly to mange, of which sarcoptic mange represent the most clinically relevant form. There is a wide range of molecules effective against sarcoptic mange, but the treatment is very challenging due to the lack of efficiency and absorption.Methods: Two cases from two different animal populations were described. A female alpaca from Romania with dermatological problems on the ears and two adult llamas, from Italy, both with intense pruritus. Combined treatment with amitraz and subcutaneous eprinomectin was administered for the alpaca, and 2% moxidectin was given to the llamas.Results: In both cases, the mites were morphologically identified as Sarcoptes scabiei. For the alpaca, negative scrapings were found only after 8 weeks of combined treatment. For the llamas, after four doses of subcutaneous moxidectin, no mites were detected in scrapings and lively hair regrowth of previously alopecic areas was visible.Conclusion: This paper aimed to present two clinical scenarios of sarcoptic mange in camelids, successfully treated with a combination of ectocides (topical amitraz and subcutaneous eprinomectin) and 2% subcutaneous moxidectin, respectively.